Didactics of communication codes in language education: dyslexia and AAC - alternative augmentative communication for a pedagogy of inclusion - V. N. Scalcione,; P. D’Antonio,; C. D’Antonio, (IJRDO- Journal of Educational Research, 2020)
Currently teachers use various methodologies to promote inclusion in subjects with specific learning disorders.Through inclusive teaching all students, not only certified ones, can make use of compensatory tools. It is a matter of promoting, on the part of the teacher, a continuous assessment, articulated daily, through the control of the notebooks and therefore of the assigned tasks and must aim at both oral and written tests: through the evaluation the teacher obtains a general performance of the class and assess the progress of all pupils. Therefore we speak of inclusive teaching also because all students have the right to take advantage of compensatory tools even if sometimes they can be used differently according to the needs of individual students. The aim of the teacher is therefore to allow the pupils to reach the maximum possible point so that they can acquire most of the skills and to make the pupil intellectually satisfied. Therefore, since teaching is a creative process, the teacher must help the student by always stimulating him to curiosity and creativity[1].  In fact, it is possible to consider "inclusion as a tool to prevent school discomfort and disaffection and create competent citizens, responsible and capable of contributing to the development of their country, fully exploiting their potential”[2].